Clinical performance of a non-rinse conditioning sealant in three paediatric dental practices: a retrospective study - D. RAM, E. MAMBER & A. B. FUKS (Paediatric Dentistry, 2005)
The present clinical retrospective study describes the retention rates of a compomer sealant (Dyract Seal, Dentsply-De Trey, Germany) with non-rinse conditioning (NRC) placed in three paediatric dentistry practices.